2019
DOI: 10.1080/19476337.2018.1554705
|View full text |Cite
|
Sign up to set email alerts
|

Maturity stages affect nutritional quality and storability of tomato cultivars

Abstract: This research was conducted to identify the optimum harvest maturity stage/s that yielded the highest nutritional quality and longest marketable shelf-life. "TY Megaton" and "Yureka" cultivars were harvested at the breaker, pink, and red stages and stored up to 20 days at 12°C with 85 ± 5% relative humidity (RH). Quality attributes, the contents of important secondary metabolites, and antioxidant activity were assessed during the storage period. Storing and marketing of tomato fruits up to 3 weeks could be pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
6
19
1
Order By: Relevance
“…The β-carotene values were 41.7 to 48.1 µg/g DW, which is consistent with values reported in the literature [69]. The lycopene values were 12.7 to 16.2 µg/g DW, which is consistent with values reported in the literature [9,70]. However, neither compound differed between coverings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The β-carotene values were 41.7 to 48.1 µg/g DW, which is consistent with values reported in the literature [69]. The lycopene values were 12.7 to 16.2 µg/g DW, which is consistent with values reported in the literature [9,70]. However, neither compound differed between coverings.…”
Section: Discussionsupporting
confidence: 91%
“…The lycopene content of the fruit harvested at the breaker stage increased throughout storage, as past studies have shown with breaker fruit stored at 12 • C [70]. While the β-carotene did not alter significantly between maturity stages.…”
Section: Discussionsupporting
confidence: 66%
“…CI was assessed visually, and the CI index was calculated according to the method described by Lee [ 10 ]. Peach fruit firmness was measured by a Rheo meter (Sun Scientific Co. Ltd., Tokyo, Japan) from 10 fruit, two measurements per fruit, by a puncture at the equator with a maximum force of 10 kg and a 3 mm diameter round stainless steel probe with a flat end, as stated by Tilahun et al [ 46 ]. PG activity and quantification of pectin were made following the methods described by Tilahun et al [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Spectral data of samples were acquired by Vis-NIR spectroscopy and a determination coefficient of 0.8 was achieved for predicting the SSC. Tilahun et al (2018) predicted beta-carotene and lycopene in tomato cultivars by NIR and chromatography spectra. More than two hundred tomato fruit samples were used at three ripening levels.…”
Section: Introductionmentioning
confidence: 99%